Pengaruh Brand Image, Brand Trust, dan Healthy Lifestyle Terhadap Minat Beli Mie Lemonilo Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro Semarang - Awaly, Ahmad Himam; Oktoriza, Linda Ayu (Jurnal EMT KITA, 2024)
This study seeks to examine how Brand Image, Brand Trust, and Healthy Lifestyle impact the purchasing interest of Lemonilo Noodles among students enrolled at the Faculty of Economics and Business, Dian Nuswantoro University, Semarang. Utilizing quantitative data, the study employs a purposive sampling technique, distributing both online questionnaires via Google Form and offline surveys to Lemonilo Noodles consumers within the aforementioned academic community. The sample size, determined through the Lemeshow formula, was set at a minimum of 96.04 respondents, rounded up to 100. The data collected underwent validation and reliability tests using SPSS. Subsequently, the research addressed basic assumptions, followed by classical assumption testing. T-tests, simultaneous tests (F), and determination tests were then conducted. The findings indicate that Brand Image, Brand Trust, and Healthy Lifestyle individually and collectively exert a positive and statistically significant influence on purchase intention. This underscores the importance of these factors in augmenting interest in Lemonilo Noodles products.